2014
DOI: 10.1002/gcc.22154
|View full text |Cite
|
Sign up to set email alerts
|

Genistein inhibits DNA methylation and increases expression of tumor suppressor genes in human breast cancer cells

Abstract: It has been previously demonstrated that genistein exhibits anticancer activity against breast cancer. However, the precise mechanisms underlying the anticancer effect of genistein, in particular the epigenetic basis, remain unclear. In this study, we investigated whether genistein could modulate the DNA methylation status and expression of cancer-related genes in breast cancer cells. We treated MCF-7 and MDA-MB-231 human breast cancer cells with genistein in vitro. We found that genistein decreased the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 39 publications
5
118
0
1
Order By: Relevance
“…Isoflavones (especially genistein) have been shown to induce epigenetic modifications [18,19,20]. To test whether dietary introduction of isoflavones will induce epigenetic modifications of promoter sites of IL-4, we tested the demethylation of specific CpG sequences in 2 sites of the IL-4 promoter region in mouse splenocytes and mesenteric lymph node cells by pyrosequencing (online suppl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoflavones (especially genistein) have been shown to induce epigenetic modifications [18,19,20]. To test whether dietary introduction of isoflavones will induce epigenetic modifications of promoter sites of IL-4, we tested the demethylation of specific CpG sequences in 2 sites of the IL-4 promoter region in mouse splenocytes and mesenteric lymph node cells by pyrosequencing (online suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Isoflavones are known to induce epigenetic modifications during cancer pathogenesis [18,19]. Epigenetic mechanisms have been implicated in allergic responses [17,27].…”
Section: Discussionmentioning
confidence: 99%
“…IFs act as phytoestrogens and prevent tumorigenesis in rodent models via various bioactivities. IFs have been previously demonstrated to target all major epigenetic mechanisms regulating gene expression in in vitro and in vivo studies (36)(37)(38)(39)(40)(41)(42)(43). Greathouse et al (44) have recently reported that genistein-mediated phosphorylation of zeste homolog 2 was able to inhibit its activity and promote benign uterine cancers in Eker rats.…”
Section: Discussionmentioning
confidence: 99%
“…The actives were positive controls or compounds that showed inhibitory activity against DNMT1 through in vitro or in vivo tests. Based on the previous research, 25 compounds were chosen as actives [11][12][13][14][15][16][17]. Their structures were obtained in SMILES format from the PubChem website at pubchem.ncbi.nlm.nih.gov [33].…”
Section: Preparing the Ligand Structurementioning
confidence: 99%
“…Natural products are promising non-nucleoside DNMTi candidates because of their relatively low toxicity and high structural diversity [10,11]. The potential of several natural products has been studied; these products have included curcumin [12], epigallocatechin (EGCG) [13], genistein [14], caffeic acid [15], psammaplin A [16], mahanine [17], and laccaic acid [16]. However, the inhibitory effects of these natural compounds are relatively low [11].…”
Section: Introductionmentioning
confidence: 99%